Direct and indirect RANK and CD40 signaling regulate the maintenance of thymic epithelial cell frequency and properties in the adult thymus - Hayama, Mio; Ishii, Hiroto; Miyauchi, Maki; Yoshida, Masaki; Hagiwara, Naho; Muramtatu, Wataru; Namiki, Kano; Endo, Rin; Miyao, Takahisa; Akiyama, Nobuko; Akiyama, Taishin (Frontiers in Immunology, 2024)
Medullary thymic epithelial cells (mTECs) play a crucial role in suppressing the onset of autoimmunity by eliminating autoreactive T cells and promoting the development of regulatory T cells in the thymus. Although mTECs undergo turnover in adults, the molecular mechanisms behind this process remain unclear. This study describes the direct and indirect roles of receptor activator of NF-κB (RANK) and CD40 signaling in TECs in the adult thymus. Flow cytometric and single-cell RNA-seq (scRNA-seq) analyses suggest that the depletion of both RANK and CD40 signaling inhibits mTEC differentiation from CCL21+ mTEC progenitors to transit-amplifying TECs in the adult thymus. Unexpectedly, this depletion also exerts indirect effects on the gene expression of TEC progenitors and cortical TECs. Additionally, the expression levels of AP-1 genes, which enable the further subdivision of TEC progenitors, are up-regulated following the depletion of RANK and CD40 signaling. Overall, our data propose that RANK and CD40 signaling cooperatively maintain mature mTEC frequency in the adult thymus and sustain the characteristics of TEC progenitors through an indirect mechanism.